2022
DOI: 10.3389/fphar.2022.927855
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Natural Polysaccharides in the Treatment of Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease that is persistent and nonspecific. There are several medications available for the treatment of UC. However, conventional UC medications have substantial adverse effects, low clinical effectiveness, and a high recurrence rate. Therefore, it is critical to discover new medicines that are both safe and effective for UC patients. Natural polysaccharides offer a wide range of pharmacological benefits, including anti-inflammatory, anti-virus, anti-tumor, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Polysaccharides extracted from Arctium lappa considerably improve gut microbiota by promoting Proteobacteria, Alcaligenaceae, Staphylococcus, and Bacteroidetes, which are beneficial for the relief of UC [41]. In addition, Rheum Tanguticum, Codonopsis pilosula, and other plant polysaccharides can regulate intestinal flora and alleviate UC [42]. In addition to polysaccharides, 5-10% of dietary protein is not absorbed as proteins and peptides when it passes through the ileum and enters the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides extracted from Arctium lappa considerably improve gut microbiota by promoting Proteobacteria, Alcaligenaceae, Staphylococcus, and Bacteroidetes, which are beneficial for the relief of UC [41]. In addition, Rheum Tanguticum, Codonopsis pilosula, and other plant polysaccharides can regulate intestinal flora and alleviate UC [42]. In addition to polysaccharides, 5-10% of dietary protein is not absorbed as proteins and peptides when it passes through the ileum and enters the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that traditional Chinese medicine has a significant effect on the treatment of NAFLD with fewer adverse reactions [ 137 ]. Polysaccharides, as a class of natural macromolecules widely present in traditional Chinese medicines (TCM), have attracted much attention due to their rich activities and reliable biosafety [ 138 , 139 , 140 , 141 ]. In recent years, it has been found that polysaccharides, especially from TCM, have the potential to prevent and treat NAFLD with diverse structures and mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Drugs loaded onto biomaterials generally exhibit large loading capacity, controllable drug release, and improved drug bioavailability, which are beneficial for maximizing their therapeutic efficacy. [18,24,25] Among these biomaterials, silk sericin (SS), a globular water-soluble protein derived from cocoons, has been shown to be an excellent bioactive natural carrier for fabricating advanced drug delivery systems. [26,27] In addition to serving as a drug carrier, SS exhibits intrinsic biological activities, such as cellular adhesion and proliferation activity, antioxidant, and anti-tyrosine properties, which can synergize with various drugs and optimize their efficacy.…”
Section: Introductionmentioning
confidence: 99%